A 12 MINUTE CONSULTATION: 12 minute consultation: a patient with nasal crusting - Yaneza, M.M.C.; Broomfield, S.J.; Morar, P. (Clinical otolaryngology, 2010)
Clin. Otolaryngol. 2010, 35, 313–320 Background:  Nasal crusting is frequently encountered by the otorhinolaryngologist and often requires no specific treatment. It is, however, important to carry out a full history and examination, followed by appropriate investigations, in order to detect the small number of cases in which crusting is caused by systemic or malignant disease. Methods:  This review was based on a literature search last performed on 30th July 2009. The MEDLINE, EMBASE and Cochrane databases were searched using the subject headings (nasal crusting OR crusts) and in combination with diagnosis, therapy and surgery. Similar searches were performed for relevant diseases, e.g. Wegener’s granulomatosis, sarcoidosis. Results were limited to English language articles including clinical trials, meta‐analyses, systematic reviews and review articles. Relevant references from selected articles were reviewed. Results:  Knowledge of the causes of nasal crusting will help to target the history, examination and investigation of patients with this condition. Screening tests for systemic conditions can be useful but most have limited sensitivity and must be interpreted cautiously. Nasal septal biopsy is indicated when there is a suspicion of malignancy, or to support a suspected diagnosis of vasculitis. The treatment offered depends upon the cause of crusting and the severity of symptoms. Conclusion:  A careful and thorough history and examination, and targeted investigation, of the patient with nasal crusting will ensure correct diagnosis and treatment of patients with this common condition.